Filsafat Ketuhanan: Interpretasi Individu Terhadap Ajaran Ketuhanan: Kajian Studi Kasus Konversi Agama - Teguh Krisnanto; Fibry Jati Nugroho; Agung Dian Rengganis (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
A person's religious experience is a very individual inner matter. Everyone experiences a spiritual experience that brings maturity in practicing the religion they believe in. In Indonesia, there are still religious conversions. This is because there are inner conflicts and conflicting feelings that result in turmoil that originates from the problems of faith faced. Religious conversion can be experienced by anyone. As experienced by AW, the conversion from Christianity to Islam. Starting from the interpretation of the understanding of divinity based on the philosophy of Divinity. This happened when AW continued his Strata-3 education. The purpose of this study is that the researcher wants to know how Mr. AW uses philosophy to question and criticize the beliefs and values ​​of Christianity until he has an interpretation of Christian teachings about God. In this study, the author uses a qualitative method with a case study approach. Where the author collects data by interviewing participants as a source of information. In addition to interviews, literature related to religious conversion is also used. Thus, the results of this study are expected to provide researchers with the reasons for AW's conversion. Recommend that religious leaders and congregations be wary of all religious philosophies. Spiritual leaders and parents can protect their congregations or children from understanding philosophical teachings that influence and shake Christian faith. There needs to be serious faith formation in the congregation to strengthen their faith and answer the challenges of understanding that can destroy Christian faith.